Infant communicative development assessed with the European Portuguese MacArthur–Bates Communicative Development Inventories short forms. Issue 5 (October 2016) - Frota, Sónia; Butler, Joseph; Correia, Susana; Severino, Cátia; Vicente, Selene; Vigário, Marina
This article describes the European Portuguese MacArthur–Bates Communicative Development Inventories short forms, the first published instruments for the assessment of language development in EP-learning infants and toddlers. Normative data from the EP population are presented, focusing on developmental trends for vocabulary learning, production of morphologically complex words and word combinations. Significant effects of gender were found for early word comprehension and production, as well as for toddlers' word production, word complexity and word combinations, with a consistent advantage for girls. By contrast, effects of socioeconomic status were limited to early word comprehension. A cross-language comparison with short form data for other languages was performed. Differences across languages only emerged for toddlers. However, effects of gender were found independently of language differences.